Pemberdayaan Perekonomian Masyarakat dengan Pemanfaatan Buah Kelapa Menjadi Olahan Makanan Lepa di Desa Merbaun, Kecamatan Amarasi Barat - Dedy Raidons; Helda Marlin (Jurnal Informasi Pengabdian Masyarakat, 2024)
This Community Service Program aims to empower the economy of the Merbaun Village community, Amarasi Barat District, through the utilization of coconut as an ingredient for the food product "Lepa." The activities are designed to enhance the knowledge and skills of the community in managing local resources in a simple, practical, and economically valuable manner. This program involves a series of training sessions covering business management, product processing, and assistance in financial reporting and product marketing. The results of the program show an increase in the understanding and ability of the community to produce and market "Lepa," which is expected to contribute to increasing family income and economic welfare. Additionally, this program provides an opportunity for partners to gain new insights into the innovative and sustainable utilization of coconut potential.